Model Pembelajaran Prodigy Berbasis Metakognitif Rekonstruktivisme Kemandirian Belajar Siswa melalui Layanan Bimbingan dan Konseling - Teuku Fadhli (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2023)
The metacognitive-based prodigy learning model in schools aims to develop thinking processes through stimulation of thoughts that do not develop through guidance and counseling services by BK teachers. The importance of students' metacognitive-based Study Program learning models so that students are able to optimally actualize themselves. So the role of the counseling teacher in guidance and counseling services is very influential on students' self-development. Therefore, the prodigy theory approach based on metacognitive reconstructivism in educational settings in schools is very influential in shaping the character of independent learning for students